2015
DOI: 10.1371/journal.pone.0132522
|View full text |Cite
|
Sign up to set email alerts
|

Selective Pressures Explain Differences in Flower Color among Gentiana lutea Populations

Abstract: Flower color variation among plant populations might reflect adaptation to local conditions such as the interacting animal community. In the northwest Iberian Peninsula, flower color of Gentiana lutea varies longitudinally among populations, ranging from orange to yellow. We explored whether flower color is locally adapted and the role of pollinators and seed predators as agents of selection by analyzing the influence of flower color on (i) pollinator visitation rate and (ii) escape from seed predation and (ii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 43 publications
3
58
3
1
Order By: Relevance
“…For example, pollinator preference for specific flower colors can reinforce reproductive isolation between sister species (Hopkins & Rausher, , ). Furthermore, spatial variation in pollinator communities can contribute to local adaptation and genetically based clines in flower color (Streisfeld & Kohn, ; Sobral et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…For example, pollinator preference for specific flower colors can reinforce reproductive isolation between sister species (Hopkins & Rausher, , ). Furthermore, spatial variation in pollinator communities can contribute to local adaptation and genetically based clines in flower color (Streisfeld & Kohn, ; Sobral et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…However, we found no evidence of local adaptation of yellow-flowering plants to the original population since the number of bumblebee visits was similar to the orange-flowering transplants in Pontón. This result differs from previous ones, indicating that flower color among G. lutea populations is related to selective pressures exerted by pollinators (Sobral et al, 2015). (Price et al, 2005), even different plant populations that share the same pollinator group receive different proportions of flower visits from each species or functional group (Fenster et al, 2004;Tastard et al, 2014).…”
contrasting
confidence: 94%
“…The fruit is an ovoid capsule, holding elliptic and winged seeds of 5 3-4 mm (Renobales, 2012). This species is a generalist that needs pollinators to seed production, being mainly pollinated by bumblebees (see Veiga et al, 2015;Sobral et al, 2015).…”
Section: Plant Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have investigated ecological interactions in the same populations (Rossi et al , ) and karyological features of the studied subspecies (Rossi et al ). Recently, several authors have studied the occurrence of different colour morphs in Spanish populations of G. lutea , and they found that pollinators and predators, but not abiotic factors, act as selective agents on flower colours (Sobral et al , Veiga et al , ). However, we did not encounter plants with different floral phenotypes in our study populations.…”
Section: Methodsmentioning
confidence: 99%